“Virus Identification for Monkeypox in Human Seminal Fluid Samples: A Systematic Review“ - Barboza, Joshuan J. (2023)
Public health officials around the world are extremely concerned about the global outbreak of monkeypox (MPX), which has been claimed to have originated in Africa. As a result, studies into the origins and reasons behind the outbreak’s rapid spread have been sped up. The goal of the current investigation is to determine whether the monkeypox virus (MPXV) is present in seminal fluid samples from MPX cases that have been verified. Up until 6 January 2023, PubMed, Scopus, Web of Science, Embase, and ScienceDirect databases were used to conduct a thorough evaluation of the literature. The search technique returned a total of 308 items. Fourteen studies reporting the presence of MPXV in the seminal fluid of MPX-confirmed cases were included after the duplicates (n = 158) and searches by title, abstract, and full text were eliminated. In 84 out of the 643 confirmed MPX cases (13.06% or n = 643), MPXV was discovered in seminal fluid. Reverse transcriptase polymerase chain reaction (RT-PCR) was used to identify MPXV, and samples taken from skin lesions (96.27%), pharynx or oropharynx (30.48%), and blood all had higher positivity rates than other samples (12.44%). Additionally, 99.85% of respondents were male with a mean age of 36, 98.45% engaged in MSM (men who have sex with men) sexual conduct, and human immunodeficiency virus (HIV) accounted for 56.9% of all STD cases. This study offers proof that MPXV can be found in the seminal fluid of MPX sufferers. Our data imply that MPXV transmission is a possibility in these samples and that MSM are more vulnerable to it. The creation of hygienic standards is essential for the early identification of MPX cases.